GrandQC: A comprehensive solution to quality control problem in digital pathology - Zhilong Weng; Alexander Seper; Alexey Pryalukhin; Fabian Mairinger; Claudia Wickenhauser; Marcus Bauer; Lennert Glamann; Hendrik Bläker; Thomas Lingscheidt; Wolfgang Hulla; Danny Jonigk; Simon Schallenberg; et al. (Nature Communications)
Abstract Histological slides contain numerous artifacts that can significantly deteriorate the performance of image analysis algorithms. Here we develop the GrandQC tool for tissue and multi-class artifact segmentation. GrandQC allows for high-precision tissue segmentation (Dice score 0.957) and segmentation of tissue without artifacts (Dice score 0.919–0.938 dependent on magnification). Slides from 19 international pathology departments digitized with the most common scanning systems and from The Cancer Genome Atlas dataset were used to establish a QC benchmark, analyzing inter-institutional, intra-institutional, temporal, and inter-scanner slide quality variations. GrandQC improves the performance of downstream image analysis algorithms. We open-source the GrandQC tool, our large manually annotated test dataset, and all QC masks for the entire TCGA cohort to address the problem of QC in digital/computational pathology. GrandQC can be used as a tool to monitor sample preparation and scanning quality in pathology departments and help to track and eliminate major artifact sources.